Carbofuran Induced Oxidative Stress in Rat Heart: Ameliorative Effect of Vitamin C. (26th December 2013) - Jaiswal, Sunil Kumar; Siddiqi, Nikhat J.; Sharma, B.
Abstract : The aim of this study was to evaluate the effect of carbofuran on the levels of certain biomarkers in heart of rat exposed to sublethal concentrations of pesticide for 30 days after each interval of 24 h. The ameliorative effect of vitamin C by pretreatment of rats was also monitored. The results indicated that the activities of acetylcholinesterase and lactate dehydrogenase (LDH) decreased significantly in rat heart tissues, the extent of inhibition being concentration dependent. In contrast, the level of LDH increased in serum. The levels of malondialdehyde, total thiols, and glutathione were significantly elevated whereas the activities of antioxidant enzymes such as superoxide dismutase, catalase, and glutathione-S-transferase were remarkably decreased in rat heart tissues. The serum concentrations of cholesterol increased by 47 and 77% and high density lipids decreased by 35 and 64%, respectively, due to exposure to 5 and 10% LD50 of carbofuran. The prior treatment of rats with vitamin C (100 mg kg −1 body weight) exerted significant ameliorative effect. The recovery was higher at low carbofuran concentration (5%) tested. The results indicated that carbofuran induced oxidative stress and caused damage to cardiac tissues, which could be recovered by prior application of vitamin C.